Effects of Marginalization on School Physical Education Programs: a Literature Review - Laureano Justin; Konukman Ferman; Gümüşdağ Hayrettin; Erdoğan Şamil; Yu Jong-Hoon; Çekin Resul (Sciendo, 2014)
The purpose of this research was to examine the causes of marginalization in Physical Education (PE) and to examine how PE teachers can counter the effects of this marginalization. Therefore, a recent literature review was conducted for the purpose of investigating the effects of marginalization. Four studies addressed feelings of burnout among PE teachers, including isolation, lack of equipment, and lack of space. Three research articles addressed communication with parents to encourage their support of PE. These three articles examined the use of PE websites as a tool to stay in constant communication with parents. In addition, one research study looked at how PE assessments needed to be consistent with other content areas and aligned with state and national standards. Moreover, one research article addressed the causes of parents' misconceptions of their children's PE programs. The final research article was a case study that related to how one teacher was able to change the parents' misconceptions about the PE programs. Results from this literature review study indicated that PE programs are being marginalized, yet there are ways for PE teachers to combat this issue.